Pseudomonas aeruginosa Implant-Associated Bone and Joint Infections: Experience in a Regional Reference Center in France - Cerioli, Matteo; Batailler, Cécile; Conrad, Anne; Roux, Sandrine; Perpoint, Thomas; Becker, Agathe; Triffault-Fillit, Claire; Lustig, Sebastien; Fessy, Michel-Henri; Laurent, Frederic; Valour, Florent; Chidiac, Christian; et al. (Frontiers in Medicine, 2020)
Background:P. aeruginosa implant-associated bone and joint infections (BJI) is considered to be one of the most difficult to treat BJI. The data focusing specifically on this pathogen are sparse, and it seems difficult to extrapolate the results obtained with Enterobacteriaceae. Methods: We performed a retrospective observation study of all P. aeruginosa implant-associated BJI diagnosed at our institution from 2011 to 2018. We defined failure as any type of relapse, including persistence of the same P. aeruginosa, superinfection by another organism(s) or any other cause of relapse such as the need for a subsequent surgery. Nonparametric statistical methods were used to compare the study groups and Kaplan-Meier curves and multivariate Cox analysis and were used to detect determinants associated with treatment failure. Results: A total of 90 patients (62% men, median age 60 years IQR 47–72) including 30 (33%) prosthetic-joint infections and 60 (66%) other implant-associated BJIs were studied. Most of them were acute (62%). During the prolonged follow-up, (median 20 months; IQR 9–37), 23 patients (26%) experienced treatment failure. Optimal surgical treatment (DAIR for acute forms, explantation, 1-stage or 2-stage exchange for others) was significantly associated with a higher success rate in the univariate analysis (p = 0.003). Sixty-four (71%) patients received effective initial treatment against P. aeruginosa administered and 81 of them (90%) did for at least 3 weeks: both these parameters correlated with a higher success rate. In the multivariate Cox-analysis optimal surgical treatment, IV effective treatment of at least 3 weeks and treatment with ciprofloxacin for at least 3 months proved to be independently associated to a better outcome in patients with P. aeruginosa implant-associated BJI. Conclusion:P. aeruginosa implant-associated BJI is one of the most difficult-to-treat BJI, with a strong impact on the prognosis of the surgical strategy. An effective initial IV antibiotic treatment for at least 3 weeks seems to be required, followed by oral ciprofloxacin for a total duration of 3 months.